A hybrid of CFD and PSO optimization design method of the integrated slipper/swashplate structure in seawater hydraulic axial piston pump. Issue 1 (31st December 2022) - Hong, Ruidong; Ji, Hui; Nie, Songlin; He, Hao; Guo, Ming; Yin, Fanglong; Yan, Xiaopeng
Abstract : An integrated slipper/swashplate structure is developed for seawater hydraulic axial piston pump. Considering the overturning moment of the integrated slipper, the transient hydrodynamic lubrication model of the integrated slipper is established, and the body-fitted grid and five-point finite difference method is employed to accurately solve the model. An optimization design method based on a hybrid of CFD (Computational Fluid Dynamics) and PSO (Particle Swarm Optimization) for the integrated slipper is proposed for the interface structure with the low leakage and power loss. The optimal sealing belt of the integrated slipper is obtained, and the leakage and power loss are reduced by 27.3% and 16.7% under the same gap size, respectively. The effects of working condition on the film-forming characteristics and power consumption characteristics of the lubricating film are analyzed based on the optimized integrated slipper. It is found that the leakage and total power loss increase significantly with the increasement of working pressure and shaft speed, and decrease with the increasement of temperature. The excellent lubrication characteristics and strong anti-overturning ability of the integrated slipper/swashplate structure can improve the performance of the seawater axial piston pump, and its optimization design method proposed in this study can provide a new reference for engineers.